Kajian Pencegahan dan Penanggulangan Kebakaran pada Pasar Tradisional Lawang - Damayanti, Fifi; Ningrum, Diana (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2021)
Â This research starts from the market paradigm associated with dirty, slum, exceeding capacity so it is prone to fire. How do you solve this problem? This study discusses what elements are improving and managing disasters in traditional markets. The originality of this research seeks to study what elements affect disaster mitigation in market buildings with two analyzes, namely: (1) analysis of existing data and (2) inductive analysis. Literature review in this study comes from PermenPU No.26 / PRT / M / 2008, specifically about the completeness of the site in the traditional market environment, rescue facilities in the traditional market environment, active protection systems and protection of traditional market buildings. This research strategy uses descriptive, qualitative strategies. Related to collecting data, this study uses field observations consisting of: field measurements, field installations, field sketches and in-depth interviews. In the analysis of research data applying two types, namely: (1) analysis of existing data and (2) inductive analysis. The results obtained in this study are summarized into 4 (four) main categories and 9 (nine) observation units / variables. The purpose of this study is a diagram about not forming fire mitigation in the traditional market Lawang